2022
DOI: 10.1101/2022.06.02.494429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multifaceted architectural framework of the mouse claustrum complex

Abstract: Accurate anatomical characterizations are necessary to investigate neural circuitry on a fine scale, but for the rodent claustrum complex (CC) this has yet to be fully accomplished. The CC is generally considered to comprise two major subdivisions, the claustrum (CL) and the dorsal endopiriform nucleus (DEn), but regional boundaries to these areas are highly debated. To address this, we conducted a multifaceted analysis of fiber- and cyto-architecture, genetic marker expression, and connectivity using mice of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 63 publications
2
29
0
Order By: Relevance
“…The RSP is uniquely positioned for use in this technique as it does not receive inputs from structures around the CLA but receives specifically dense innervation from the CLA itself. We found that CLA RSP neurons span the rostrocaudal axis of the CLA and align with previously identified markers of the CLA “core” (34, 38, 39, 53). Retrograde tracing from RSP offered a simple method for accurately assessing the anatomical and physiological features CLA neurons in later experiments.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The RSP is uniquely positioned for use in this technique as it does not receive inputs from structures around the CLA but receives specifically dense innervation from the CLA itself. We found that CLA RSP neurons span the rostrocaudal axis of the CLA and align with previously identified markers of the CLA “core” (34, 38, 39, 53). Retrograde tracing from RSP offered a simple method for accurately assessing the anatomical and physiological features CLA neurons in later experiments.…”
Section: Discussionsupporting
confidence: 87%
“…S1). Further, this strategy consistently demonstrated that retrosplenial-projecting CLA (CLA RSP ) neurons could be found along the whole CLA length, as defined by other sources (33)(34)(35)(36). Moreover, the level of overlap between CLA neurons projecting to different regions of RSP varied depending on the injection site (Fig.…”
Section: Anatomical Delineation Of Cla In Mice Via Retrograde Tracingmentioning
confidence: 66%
See 2 more Smart Citations
“…While the latter is not easily identified with classical histological stains in the mouse brain, it has been reported that the claustrum is surrounded by densely myelinated fibers ( Wang et al. 2017 , 2022 ; Grimstvedt et al. 2022 ).…”
Section: Introductionmentioning
confidence: 98%